PERLAKUAN AKUNTANSI UNTUK HERITAGE ASSET PADA PENINGGALAN PURBAKALA - Langgeng Prayitno Utomo (JAD: Jurnal Riset Akuntansi dan Keuangan Dewantara, 2021)
This study aims to assess the accounting treatment for heritage assets at the Mojokerto Cultural Heritage Preservation Center. This study used a qualitative approach. The data used was primary data obtained through in-depth interviews with informants. In addition, secondary data in the form of financial reports were also used to complete the research. The analysis tool used source triangulation. The results showed that the management of historical assets at the Mojokerto Cultural Heritage Preservation Center was in accordance with the Government Accounting Standard Guidelines 07, which was recognized after a letter of determination from the authorities was issued. Although the valuation of historic assets was still having difficulty determining the method that was in accordance with Government Accounting Standard Guidelines 07, namely historical assets were valued at zero and disclosed in the Notes to Financial Statements without value by only stating the number of units of the historic asset and only recording the price of the fee for the discovery of historical objects at the registration section at the Mojokerto Cultural Conservation Preservation Center